2005
DOI: 10.1094/cc-82-0504
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline‐Carbonate Noodles from Hard Winter Wheat Flours Varying in Protein, Swelling Power, and Polyphenol Oxidase Activity

Abstract: Cereal Chem. 82(5):504-516The effects of wheat protein and starch on yellow-alkaline noodles have not been fully clarified. Twenty-four hard winter wheats with varying protein, hot-water swelling power (SP 95 ), and polyphenol oxidase (PPO) activity were milled into long-patent and short-patent flours. Protein, SP 95 , and PPO activity in the 48 flours were 8.2-12.9%, 16.2-24.1 g/g, and 80-157 ∆A 480 /mg of protein/min, respectively. Lightness of raw noodles declined with increasing protein and PPO levels but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
2
23
0
1
Order By: Relevance
“…The major quality criteria for noodle wheat are bran colour, kernel hardness, protein content, dough strength, and starch pasting properties (Crosbie & Ross, 2004). Execution of correct milling procedures is very critical to ensure the resulting noodle flour has bright colour, low ash content, low level of damaged starch, and fine particles (Park, Baik, 2004;Ross et al, 1997;Zhao, Seib, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The major quality criteria for noodle wheat are bran colour, kernel hardness, protein content, dough strength, and starch pasting properties (Crosbie & Ross, 2004). Execution of correct milling procedures is very critical to ensure the resulting noodle flour has bright colour, low ash content, low level of damaged starch, and fine particles (Park, Baik, 2004;Ross et al, 1997;Zhao, Seib, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers concluded that high starch pasting properties or high hot water swelling power, which are related, are negatively correlated with hardness and can therefore result in lower quality YANs (Miskelly and Moss 1985;Konik et al 1994;Batey et al 1997;Crosbie et al 1999;Zhao and Seib 2005;Ross 2006). However, some reports also indicate that high starch pasting or swelling power may increase noodle smoothness and elasticity (Konik et al 1994;Batey et al 1997;Akashi et al 1999;Zhao and Seib 2005;Ross 2006;Tanaka et al 2006).…”
Section: Dual-purpose Hard White Wheatmentioning
confidence: 99%
“…However, some reports also indicate that high starch pasting or swelling power may increase noodle smoothness and elasticity (Konik et al 1994;Batey et al 1997;Akashi et al 1999;Zhao and Seib 2005;Ross 2006;Tanaka et al 2006). This presents a conflict where increased starch pasting properties improve some aspects of YAN quality but compromise noodle hardness.…”
Section: Dual-purpose Hard White Wheatmentioning
confidence: 99%
See 2 more Smart Citations